Prototipe Sistem Pendukung Keputusan Pemilihan Karyawan Teladan dengan Menggunakan Metode Profile Matching - Ruben Edward (Universitas Indraprasta PGRI Jakarta, 2019)
The high performance of workers is closely related to the reward system. The award in the form of selecting exemplary employees encourages the creation of self-employed, disciplined, and achieving employees. Improper employee role choices can lead to injustice and impact on employee motivation. Number of employees, the number of criteria in the assessment, the potential of subjective judgment, and the system is still a simple manual of work processes exemplary employees in PT SRI takes a long time. To solve the problems that occur, then prepare a decision support system for the creation of a more effective and efficient decision. With the new system is expected to enter in the search data, calculate in the assessment of selection of exemplary employees, and decision decision. In making this Decision Support System will use the method of Matching Case Study in PT SRI. This study discusses the analysis of the work, skills or skills, work attitude, knowledge (knowledge), Personality and socialization are categorized in the core and secondary factors using GAP methods Analysis in accordance with Profile Matching method. The result of the research is a decision support system capable of providing effective and efficient